Molecular imaging of tissue repair after myocardial infarction : preclinical evaluation of novel 68Ga-labeled PET tracers - Kiugel, Max (fi=Turun yliopisto|en=University of Turku|, 2018)
Congestive heart failure (HF) develops soon after acute myocardial infarction (AMI) in almost 25% of initial survivors. Modern cardiac imaging methods are useful for HF diagnostics and, possibly, the detection of underlying molecular mechanisms involved in myocardial repair. CD44, a cell-surface glycoprotein, is involved in various cellular functions, including cell proliferation, adhesion, migration and lymphocyte activation. Integrins are transmembrane proteins involved in various signaling pathways related to inflammation, angiogenesis and fibrosis. Expression of proteolytic matrix metalloproteinases 2 and 9 (MMP-2/9) also associates with extracellular matrix remodeling. The purpose of this thesis was to evaluate novel Gallium-68 labeled imaging agents targeting αvβ3 integrin, MMP-2/9, or CD44, for positron emission tomography (PET) imaging of post-MI repair in a surgical rat model. The MMP- 2/9 targeting tracer watarkias also evaluated for imaging of atherosclerotic lesions in a hypercholesterolemic mouse model. In vivo PET imaging, ex vivo biodistribution, ex vivo autoradiography, and immunohistochemistry were utilized to assess tracer stability, uptake in various tissues, as well as uptake correlation with various cellular level processes. Of the studied tracers, αvβ3 integrin targeting tracer showed the most optimal characteristics for imaging of myocardial healing processes. Tracer uptake in the damaged myocardium was clearly visible in vivo, and blood clearance as well as tracer stability were sufficient. The CD44 targeting tracer showed initial potential warranting further development, as the tracer uptake was associated with myocardial inflammation. MMP-2/9 targeted imaging showed significant limitations due to tracer instability and slow clearance. In conclusion, imaging of αvβ3 integrin expression is a potential tool for the purpose of evaluating myocardial repair after MI.

Sydänkudoksen infarktinjälkeisen paranemisen molekyylikuvantaminen : uusien 68Ga-leimattujen merkkiaineiden prekliininen arviointi Sydämen vajaatoiminta kehittyy pian akuutin sydäninfarktin jälkeen lähes 25 prosentille eloonjääneistä. Nykyaikaiset sydämen kuvantamismenetelmät ovat hyödyllisiä diagnostiikassa ja mahdollisesti sydänlihaksen muovautumiseen liittyvien molekyylimekanismien havaitsemisessa. Solupinnan glykoproteiini CD44 osallistuu erilaisiin soluvälitteisiin toimintoihin, kuten proliferaatioon, adheesioon, migraatioon ja lymfosyyttien aktivaatioon. Integriinit ovat transmembraaniproteiineja, jotka osallistuvat erilaisiin signalointireitteihin liittyen tulehdukseen, angiogeneesiin ja fibroosiin. Proteolyyttisten matriksin metalloproteinaasi 2:n ja 9:n (MMP-2/9) ilmentyminen liittyy niin ikään solunulkoisen matriksin uudelleenmuovautumiseen. Tämän väitöskirjan tarkoituksena on arvioida uusia Gallium-68-leimattuja koettimia positroniemissiotomografiaa (PET) varten. Tutkitut koettimet kohdistuvat joko αvβ3-integriiniin, MMP-2/9:ään tai CD44:ään. Tutkimus toteutettiin infarktinjälkeisen sydämen vajaatoiminnan kirurgisessa rottamallissa. MMP-2/9-koetinta arvioitiin myös ateroskleroottisten muutosten kuvantamiseen hyperkolesterolemisessa hiirimallissa. αvβ3-integriiniin kohdentuvan merkkiaineen kertymä näkyi selkeästi in vivo, ja veren puhdistuma sekä merkkiaineen stabiilisuus olivat riittävät. CD44 kuvantamiskohteena osoitti alkuvaiheen potentiaalia, joka mahdollistaa jatkokehityksen, sillä merkkiaineen kertymä assosioitui infarktinjälkeiseen tulehdusreaktioon. MMP-2/9- kohdennetulle kuvantamiselle puolestaan ilmeni merkittäviä rajoituksia merkkiaineiden epävakauden ja hitaan veripuhdistuman vuoksi Yhteenvetona voidaan todeta, että αvβ3-integriinifragmentin kuvantaminen on potentiaalinen työkalu sydänlihaksen paranemisprosessien arvioimiseksi akuutin sydäninfarktin jälkeen.